2021
DOI: 10.1111/are.15501
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and impact of sublethal exposure to commonly used surfactants sodium dodecyl sulphate, cetylpyridinium chloride and sodium laureth sulphate on oxidative stress enzymes in oligochaete worm Branchiura sowerbyi (Beddard, 1892)

Abstract: The current study aimed to determine the detrimental effects of sodium dodecyl sulphate (SDS), cetylpyridinium chloride (CPC), and sodium laureth sulphate (SLES) on survival rate and oxidative stress enzymes in Branchiura sowerbyi (Beddard, 1892). The 96 h LC50 values of SDS, CPC and SLES to Branchiura sowerbyi were estimated to be 8.27, 0.12 and 19.58 mg/L, respectively. Moreover, surfactant toxicity was projected using general threshold survival models (GUTS) in terms of required data sets and fit performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Our results suggest that CPC and ZIF-NPs may also play a synergistic role in inducing oxidative stress in zebrafish larvae, as indicated by the notable increases in the ROS and MDA levels in the combined exposure groups and the significantly interactive effect predicated by the GzLM analysis. Numerous studies have demonstrated that oxidative stress is a common response in aquatic species to environmental pollutants, including NPs [20][21][22] and CPC [13][14][15][16]. Generally, organisms have evolved many enzymes (e.g., SOD, CAT, Glutathione S-Transferase, Glutathione Peroxidase, and Ascorbate Peroxidase) and antioxidants (e.g., GSH and Alpha-lipoic Acid) to scavenge excess ROS and protect cells from severe oxidative damage [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that CPC and ZIF-NPs may also play a synergistic role in inducing oxidative stress in zebrafish larvae, as indicated by the notable increases in the ROS and MDA levels in the combined exposure groups and the significantly interactive effect predicated by the GzLM analysis. Numerous studies have demonstrated that oxidative stress is a common response in aquatic species to environmental pollutants, including NPs [20][21][22] and CPC [13][14][15][16]. Generally, organisms have evolved many enzymes (e.g., SOD, CAT, Glutathione S-Transferase, Glutathione Peroxidase, and Ascorbate Peroxidase) and antioxidants (e.g., GSH and Alpha-lipoic Acid) to scavenge excess ROS and protect cells from severe oxidative damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…Using rat thymic lymphocytes, Imai et al [12] found that CPC exerted cytotoxic effects under oxidative stress conditions by increasing intracellular Zn 2+ concentration and decreasing the cellular content of nonprotein thiols. In recent years, Bhattacharya and colleagues found that sublethal CPC exposure could adversely affect the antioxidant enzymes in aquatic worms and common carp [13][14][15]. Our previous study also suggested that CPC at 400 µg/L significantly elevated the reactive oxygen species (ROS), superoxide dismutase (SOD), and glutathione (GSH) levels in zebrafish larvae [16].…”
Section: Introductionmentioning
confidence: 89%